The Effect of Dragon Fruit Juice and Honey On The Improvement of Pregnant Women’s Hb - Mulyani, Yanyan; Sari, Dewi Nurlaela (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Anemia in pregnant women is an indicator of malnutrition and ill health. One of the ways to prevent anemia is by using natural ingredients as an alternative to increase Hb, is dragon fruit and honey. The aim of this research is to find out the effect of dragon fruit juice and honey on increasing the Hb of pregnant women. The research method used a Quasi-experimental design. The population and sample of the study were 30 pregnant women in the first to third trimesters, which were divided into cases and controls. The results showed that there was no significant effect of dragon fruit juice and honey on the increase in Hb of pregnant women with a p-value of 0.719. The conclusion is that dragon fruit juice and honey are not the only interventions to increase hemoglobin levels in pregnant women, but still need iron drugs and good nutrition.